The impacts of information on returns from farming: Evidence from a nationally representative farm survey in India - Birthal, Pratap S.; Kumar, Shiv; Negi, Digvijay S.; Roy, Devesh (Wiley, 2015)
Using a nationally representative sample of farm households from India, this paper examines the impact of use of information on net farm incomes. Employing methodologies that mitigate potential biases in the estimation of the impact, the empirical results show that farmers who use information realize over 12% higher net returns per hectare. The paper also establishes a pecking order in access to information. Small farmers and those at the bottom of social hierarchy (based on caste) have access to fewer information sources, and they depend more on informal social networks and input dealers for their information needs. The larger farmers and those from upper caste rely relatively more on sources such as radio, television and newspaper.